Improving Students' Literacy Skills in Learning Physical Education, Sports and Health through Zoom Meetings - Apristi, Intan Risky Nur; Maryanti, Rina (LPPM Universitas Jenderal Achmad Yani, 2021)
In the current pandemic era, learning between teachers and students is less effective because teaching and learning activities take place at home. Community service activities in the form of Kuliah Kerja Nyata Tematik described in this paper aim to increase student interest in learning, as well as make it easier for teachers, students and parents even though the learning process takes place at home. The activities are in the form of learning physical education, sports and health, which are carried out online through the Zoom Meeting application, which emphasizes literacy. The method in this community service activity uses descriptive quantitative research with random sampling technique and uses a pretest-posttest design. The results of the activity showed that there was a good increase in students' knowledge in learning physical education of sports and health as well as students' enthusiasm for physical education of sports and health. This is indicated by the posttest average value of 92.51 %, which is greater than the pre-test average value of only 18.33 %. Thus, the emphasis on literacy aspects in elementary school students can be used in learning physical education, sports and health.